The ANALYSIS AND MAPPING OF TEMPORARY SHELTERS (CASE STUDY: JAMBI LUAR KOTA SUBDISTRICT, MUARO JAMBI REGENCY) - Augina Mekarisce, Arnild; Rahayu Ningsih, Vinna; Rodhiyah, Zuli (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACT Background: The population of Jambi Luar Kota Subdistrict in 2020 is 62.687 people, with the development of an increasing population, it will affect the increase in the amount of waste scattered in illegal locations, so it is increasingly necessary to improve the availability of Temporary Waste Shelters. Objective: The purpose of this study was to analyze and to map temporary waste shelters in Jambi Luar Kota Subdistrict, Muaro Jambi Regency.. Method: Descriptive research with the results of mapping temporary waste shelters based on Global Positioning System and Geographic Information System, data using total sampling in Jambi Luar Kota Subdistrict. The data analysis used is descriptive analysis and is presented in the form of output in the form of maps and tabulation of data. Results: The results showed that in Jambi Luar Kota Sub-district there were 36 illegal temporary waste shelters, almost all with a waste volume of 1-49 m3 (91.67%), most of them were located near neighborhood roads (77.78%), and most of them were at medium and high population density levels (80.56%). Furthermore, according to SNI 19-2454-2002, the minimum standard is 167 legal temporary waste containers. Conclution: The minimum standard for temporary waste shelters in the Jambi Luar Kota Subdistrict is 167 points, which can be mapped based on population density figures and qualified land availability. Keywords: analysis, mapping, temporary waste shelters